2019
DOI: 10.1186/s13098-019-0436-8
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to reverse cardiac lipotoxicity by aerobic interval training in a high-fat diet- and streptozotocin-induced type 2 diabetes rat model

Abstract: Background Diabetes mellitus (DM) is an important risk factor for cardiovascular disease. Aerobic interval training (AIT) has been recommended to patients as a non-pharmacological strategy to manage DM. However, little is known about whether AIT intervention at the onset of DM will reverse the process of diabetic cardiomyopathy (DCM). In this study, we sought to evaluate whether AIT can reverse the process of DCM and explore the underlying mechanisms. Methods Fifty Wist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…In correlation with earlier observation, an increase in FFAs was also observed in obese rats [ 61 ]. Histology and cardiac tissue findings have also shown that within cardiomyocytes, DCM hearts mount up lipid drops, followed by elevated levels of FFA [ 62 ]. Induced by a mismatch between fatty acid uptake and oxidation, the accumulation of triglycerides in the heart develops as a determinant of cardiac damage, primarily through accumulation of free radicals and successive activation of apoptosis [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In correlation with earlier observation, an increase in FFAs was also observed in obese rats [ 61 ]. Histology and cardiac tissue findings have also shown that within cardiomyocytes, DCM hearts mount up lipid drops, followed by elevated levels of FFA [ 62 ]. Induced by a mismatch between fatty acid uptake and oxidation, the accumulation of triglycerides in the heart develops as a determinant of cardiac damage, primarily through accumulation of free radicals and successive activation of apoptosis [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our nding of reduced PLIN5 levels in hearts with greater FLAG-MCAD expression suggest that rAAV6:MCAD treatment can reduce overall lipid accumulation in the diabetic heart, although the effect was mild and was not su cient to improve diastolic function. An 8-week exercise training program initiated 2 weeks after the induction of diabetes in rats prevented cardiac lipid accumulation, and this was associated with preserved diastolic and systolic function [70]. Thus, therapeutic strategies that have a more profound effect on reducing cardiac steatosis are likely to be more successful than rAAV6:MCAD gene therapy at improving outcomes in settings of diabetes.…”
Section: Favorable Effects Of Raav6:mcad Treatment On Lipid Accumulat...mentioning
confidence: 99%
“…The heart function highly depends on the capacity of the metabolism. Cd increased the weight of the heart in a rat model [ 47 ]. Similarly, another study showed that toxic chemicals increase organ weight due to the accumulation of lipids and inflammation [ 14 ].…”
Section: Cadmium-associated Cardiotoxicity Via Lipid Metabolismmentioning
confidence: 99%
“…During diabetic cardiomyopathy, there is an elevated FFA level which contributes to lipid accumulation in the heart. Also, the unbalance between the fatty acid uptake and its oxidation leads to TG accumulation, such as cardiac lipotoxicity, and decreases ATP in the heart, potentially leading to cardiac damage [ 47 ].…”
Section: Cadmium-associated Cardiotoxicity Via Lipid Metabolismmentioning
confidence: 99%